Effects of Fluoxetine and Venlafaxine on the Salivary Gland - Experimental Study - Silva, Silvana da; Azevedo, Luciana Reis de; Lima, Antônio Adilson Soares de; França, Beatriz Helena Sottile; Machado, Maria Ângela Naval; Johann, Aline Cristina Batista Rodrigues; Grégio, Ana Maria Trindade (IntechOpen, 2012)
None